Lean six sigma framework to improve the assembly process at a printer manufacturing company - Abdullah, Rohana; Lee, Hui Kean; Abdul Rasib, Amir Hamzah; Mansoor, Hamdan O. (Penerbit UTeM, 2023)
The printer manufacturing company under study was looking for ways to continuously improve the manufacturing process transparency, compliance and control to manage process variations and waste elimination. This study aims to apply Six Sigma framework to aid in the defect reduction at a printer manufacturing company specifically the molding process. The systematic Six Sigma Define, Measure, Improve, Analyse, and Control (DMAIC) framework was used as a powerful diagnostic tool that has been proven to improve processes by reducing or eliminating the process variations. The technique used together with the Lean Kaizen tool has enabled the possibility of identifying the defect waste occurrences prior to focusing on the root cause of the problems and eliminating them. Five proposals for improvements were identified and a control plan was devised for the management to carry out in order to achieve a more robust and leaner manufacturing. As a result, a 25% reduction in defect rates were observed with the mold process now able to meet the customer specification with process